An XMM-Newton study of the mixed-morphology supernova remnant W28. Issue Volume 9:Issue S296(2013) (29th January 2014) - Zhou, Ping; Safi-Harb, Samar; Chen, Yang; Zhang, Xiao
Abstract: We perform an XMM -Newton study of the mixed-morphology supernova remnant (MMSNR) W28. The X-ray spectrum arising from the northeastern shell consists of a thermal component plus a non-thermal power-law component with a hard photon index ( 1.5). Non-thermal bremsstrahlung is the most favourible origin of the hard X-ray emission. The gas in the SNR interior is centrally peaked and best described by a two-temperature thermal model. We found a non-uniform absorption column density and temperature profile for the central gas, indicating that the remnant is evolving in a non-uniform environment with denser material in the east. We argue that the cloudlet evaporation is an indispensable process to explain both the spectral properties and the clumpiness in the X-ray emission.